Beauty Privilege dalam Film Imperfect - Ahsanu Amalaa (Syams, 2022)
Abstract: The study on "Beauty Privilege in the Film Imperfect" aims to explore the representation of beauty standards and its impact on the characters in the film. The research focuses on the correlation between physical appearance and the privileges or disadvantages the characters experience. Through a qualitative content analysis, the study examines the way the characters are portrayed based on their physical appearance and the effect it has on their relationships, opportunities, and personal growth. The results of this study contribute to a deeper understanding of the impact of beauty privilege in the media and its influence on the audience's perception of beauty.